A Comparative Study on the Students’ Perception on the Effectiveness of English Language Skills of English Language Education Students during Online Learning and Face-to-face Learning - Muhammad Miftah Fauzan; Ulfa Kurnia Citra; Geminastiti Sakkir (Journal of Excellence in English Language Education, 2022)
The objective of this research was to determine the perceptions of English education students regarding their English skills during online learning and face-to-face learning. The research was conducted at the faculty of language and literature, majoring in English Education. The population in this research were students of English language education class 2020. The instruments used in this research were interviews and documentation. Based on the results of the research, researchers found that students' perceptions of online learning and face-to-face learning, face-to-face learning became the preferred choice as a better learning system to improve the effectiveness of students' English skills.